Osteo-odonto-keratoprosthesis (OOKP) and the testing of three different adhesives for bonding bovine teeth with optical poly-(methyl methacrylate) (PMMA) cylinder. Issue 7 (13th July 2013) - Weisshuhn, K; Berg, I; Tinner, D; Kunz, C; Bornstein, M M; Steineck, M; Hille, K; Goldblum, D
Abstract : Aim: Preparation of the lamina during osteo-odonto-keratoprosthesis (OOKP) design is complex, and its longevity and watertightness important. To date, only acrylic bone cements have been used for bonding the optical cylinder to the tooth dentine. Our aim was to evaluate different dental adhesives for OOKP preparation. Methods: Specimens of bovine teeth were produced by preparing 1.5-mm thick dentine slices with holes having a diameter of 3.5 mm. Each group (n=10 per group) was luted with either classic poly-(methyl methacrylate) (PMMA) bone cement, universal resin cement or glass ionomer cement. All specimens underwent force measurement using a uniaxial traction machine. Results: The highest mean force required to break the bond was measured for PMMA bone cement (128.2 N) followed by universal resin cement (127.9 N), with no statistically significant difference. Glass ionomer cement showed significantly lower force resistance (78.1 N). Conclusions: Excellent bonding strength combined with easy application was found for universal resin cement, and thus, it is a potential alternative to acrylic bone cement in OOKP preparation.